Staphylococcus aureus: an underestimated factor in the pathogenesis of atopic dermatitis? - Blicharz, Leszek; Rudnicka, Lidia; Samochocki, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2019)
Atopic dermatitis is a common, recurrent pruritic dermatosis with a complex pathogenesis. It has been associated with disordered patterns of immunological response and impaired epithelial barrier integrity. These features predispose the patients to robust colonization of skin lesions by Staphylococcus aureus. Virulence factors of S. aureus (e.g. superantigens, - and -toxin, protein A) have been shown to exacerbate and perpetuate the course of atopic dermatitis. Novel therapeutic options with potential for restoring natural microbiome composition are being elaborated and may enter clinical practice in the future.